World Economic Outlook, April 1989. (World Economic Outlook; World Economic Outlook, 1989)
This paper highlights that the world economic condition improved significantly during 1988. In industrial countries, output growth strengthened markedly in an environment of moderate inflation. World trade expanded at its fastest rate since 1984, which had important spillover effects on many developing countries, particularly the exporters of manufactures; significant progress was made in reducing external imbalances among the major industrial countries; and the aggregate debt-to-exports ratio of developing countries was reduced. At the same time, several aspects of the current situation continue to demand the attention of policymakers.